PERSEPSI MASYARAKAT TERHADAP ADANYA SANGSI ADAT ( Studi Kasus di Desa Pinang Merah Kecamatan Pamenang Barat Kabupaten Merangin Provinsi Jambi ) - Uying Hapid Alatas; Sri Utami (Jendela PLS: Jurnal Cendekiawan Ilmiah Pendidikan Luar Sekolah, 2021)
Customary law is a rule of human behavior in everyday life, always respected and respected because it has legal consequences or sanctions for violations that have been committed. However, the facts in the field show that many customary violations occur every year. The most common violation is kawin lari. The purpose of this research is to find out why the kawin lari customary violation is increasing in Pinang Merah Village and to find out whether the implementation of customary sanctions for kawin lari is in accordance with the customary rules that apply in Pinang Merah Village and to find out how the community's perception of the traditional kawin lari sanction in Pinang Village. Red. This research uses a case study approach with descriptive qualitative research methods. The collection technique uses observation, interview and documentation. The informants in this study amounted to 5 (five) people with the informant selection technique using purposive sampling. Data analysis techniques in this study were data reduction, data presentation and conclusions. Techniques for ensuring the validity of data Credibility, Transferability, Dependability and Comfirmability. Based on the results of data analysis, it was found that the increase in violations of the kawin lari custom was due to the lack of parental supervision and guidance towards children. Children are not well controlled, which results in children engaging in promiscuity. Elopement is one of the consequences of promiscuity. For the implementation of customary sanctions, it was found that the implementation of the traditional kawin lari sanction in Pinang Merah Village has not been implemented properly. Because there are still many violations of the kawin lari custom. Meanwhile, the community's perception of the kawin lari customary sanction is that it is a rule that must be obeyed by the community. sanctions are a hereditary inheritance from their ancient ancestors and are still used today. However, in reality, the customary sanction of kawin lari has not been implemented properly because there is still selective cutting or favoritism between the community. The suggestion in this research is that the community should obey the village customary rules that apply in Pinang Merah Village by paying customary sanctions given by the customary institution as a sign of having done something wrong. Customary institutions in order to provide understanding to the community to follow the customary rules of Pianang Merah Village, in order to reduce violations of customary sanctions.